Parental divorce homogamy and its effect on separation from cohabitation and marriage - Sanna Kailaheimo-Lönnqvist; Anette Fasang; Marika Jalovaara; Emanuela Struffolino (Suomen akatemia, 2022)
Numerous studies have shown that parental divorce increases children’s divorce risk. We
extend this literature by assessing how parental divorce on both sides of a (potential) couple
affects their partnering dynamics. Specifically, we explore 1) whether there is parental divorce
homogamy and whether the parental divorce of both partners adds to the dissolution of both 2)
cohabiting and 3) married unions. Our analyses use event history models on high-quality
Finnish Census Panel data covering 28,021 cohabiting and marital partnerships between ages
18 and 45. We found substantial parental divorce homogamy in that children who experienced
parental divorce are 13% more likely to cohabit with and 17% more likely to marry a fellow
child of divorce. Moreover, contrary to evidence from the United States and Norway, our
findings for Finland support an additive, not a multiplicative, effect. Here, both partners’
parental divorce increases their offspring’s dissolution risk by 20% for cohabitation and 70%
for marriage compared to couples where neither of their parents are divorced. We conclude that
parental divorce on both sides of a couple affects family formation processes at multiple stages.
In Finland, these effects are notably less than previously found in the United States. This is
likely because cohabitation and separation are wide-spread and socially accepted in Finland
and an expansive welfare state buffers the socio-economic consequences of divorce.